2002
DOI: 10.1007/s00221-002-1182-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions in the newborn piglet in the first 24 h after hypoxia-ischemia

Abstract: The purpose of this study was to investigate whether combined inhibition of neuronal and inducible nitric oxide synthase (NOS) by 2-iminobiotin, free radical scavenging by allopurinol, and non-protein-bound iron chelation with deferoxamine improved cerebral oxygenation, electrocortical brain activity, and brain energy status during the first 24 h after hypoxia-ischemia (HI) in the newborn piglet. Forty-three newborn piglets were subjected to 1 h of severe HI by occluding both carotid arteries and phosphorous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
3
16
1
Order By: Relevance
“…Increased CBV may indicate pronounced vasodilation in cerebral microcirculation due to exhausted autoregulatory vasodilation (14,23). Another factor influencing the increase in THI is the increase in oxygenated Hb content that results from decreased cerebral oxygen utilization caused by increased brain damage (24). Accordingly, FTOE was decreased in HIϩVEH piglets, as reported previously (14).…”
Section: Discussionsupporting
confidence: 54%
“…Increased CBV may indicate pronounced vasodilation in cerebral microcirculation due to exhausted autoregulatory vasodilation (14,23). Another factor influencing the increase in THI is the increase in oxygenated Hb content that results from decreased cerebral oxygen utilization caused by increased brain damage (24). Accordingly, FTOE was decreased in HIϩVEH piglets, as reported previously (14).…”
Section: Discussionsupporting
confidence: 54%
“…Also at the 20 h mark, the [HHb] of the insult-group piglets had a statistically significant correlation with the duration of ischemia (p Ͻ 0.05). However, the fact that there was only a significant difference at one time point-in addition to the results of Peeters-Scholte et al, (19) who found no change in [HHb] from baseline out to 24 h after severe hypoxia-ischemia in piglets-refutes the idea of using [HHb] in a prognostic capacity. In a previous study from our group, CMRO 2 was monitored for 6 h after resuscitation in piglets subjected to 30 min of hypoxia-ischemia (12); in support of the results from the present study, even though hypoxia-ischemia caused a significant and persistent 25% reduction in CMRO 2 , there were no group effects with the parameters used to determine CMRO 2 .…”
Section: Discussioncontrasting
confidence: 44%
“…All parameters were averaged over the last three time points; i.e., after general of metabolism, and these signals have been noticeably insensitive to other markers of brain injury (23,25,27).…”
Section: Resultsmentioning
confidence: 99%